1995
DOI: 10.1111/j.1745-3984.1995.tb00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Approaches and Cognitive Styles

Abstract: The outcomes on multiple‐choice tests and performance‐based assessments for field‐independent and field‐dependent students were examined. A substantial interaction between cognitive style and assessment approach was found. Results suggested that performance‐based assessment tended to favor field‐independent subjects. Dependent on the purpose and intended use of assessment, this finding may raise concerns for validity based on either fairness or curriculum relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…First, an examination of the nature of FD and FI cognitive styles as reflected by GEFT scores is necessary to gain a deeper understanding of the results and implications of the current study. In taking the GEFT, a subject is required to direct his or her selective attention to specific and relevant cues while controlling for more salient irrelevant features of the context ( Lu & Suen, 1995 ). As pointed out by Zelinker (1989) , the difference between FD and FI cognitive styles rest with a person’s capability for selective attention, attention control, and stimulus organization.…”
Section: Discussionmentioning
confidence: 99%
“…First, an examination of the nature of FD and FI cognitive styles as reflected by GEFT scores is necessary to gain a deeper understanding of the results and implications of the current study. In taking the GEFT, a subject is required to direct his or her selective attention to specific and relevant cues while controlling for more salient irrelevant features of the context ( Lu & Suen, 1995 ). As pointed out by Zelinker (1989) , the difference between FD and FI cognitive styles rest with a person’s capability for selective attention, attention control, and stimulus organization.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that provision of contextual support can eliminate performance differences between FDs and FIs, or even produce a performance advantage for FDs. Lu and Suen (1995) found that FD university students obtained lower grades than FI students on "performance-based" course assessments (i.e., take-home projects), but scored as well as FI students on multiplechoice tests covering the same content. Rickards, Fajen, Sullivan, and Gillespie (1997) had university students read two structurally similar passages in either a notetaking or no-notetaking condition.…”
Section: Fdi: Style or Ability?mentioning
confidence: 94%
“…A substantial number of studies have been conducted that provide normative data for a wide range of American samples at various grades, from elementary school to undergraduate training (Carter & Loo, 1980;Lu & Suen, 1995;Murphy, Casey, Day, & Young, 1997;Onwuegbuzie & Daley, 1997;Cakan, 2000). The test has also been translated into other languages and administered to various samples from German, Russian, Malaysian, Canadlan, Pakistani, Nigerian, Egyptian, Austrahan , and Mexican-American cultures (Firth & Fitzgerald, 1985;Alvi, Khan, & Vegeris, 1986;McRae & Young, 1988;Mshelia & Lapidus, 1990;Kush, 1996;Elwan, 1997;Kuhnen, Hannover, Roeder, Shah, Schubert, Upmeyer, & Zakaria, 2001).…”
mentioning
confidence: 99%